AN ANALYSIS OF CULTURE SHOCK EXPERIENCED BY DANISH TOURISTS IN RELATION TO SINGARAJA CULTURAL VISIT - ., Kadek Toni Sumartawan; ., Dr. I Gede Budasi, M.Ed.; ., Nyoman Karina Wedhanti, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk menganalisis syok budaya yang dialami oleh orang Denmark di Singaraja. Jenis penelitian ini adalah deskriptif kualitatif. Peneliti menganalisis fungsi bahasa dari culture shock, bagaimana cara mengatasi budaya Bali, dan bagaimana caranya beradaptasi dengan budaya. Ada dua bentuk di culture shock, diantaranya adalah verbal komunikasi dan non-verbal komunikasi. Subjek di dalam penelitian ini adalah tiga orang Denmark yang tinggal di Singaraja. Data ini diambil melalui wawancara semi-struktur dan semi secara tidak terstruktur Data tersebut diperoleh melalui wawancara dan rekaman suara. Teori yang digunakan untuk menganalisis data adalah teori dari Pederson (1995). Hasil dari penelitian ini terbukti bakwa ada dua puluh syok budaya di verbal komunikasi dan non-verbal komunikasi dari orang Denmark di Singaraja. Ada sepuluh syok budaya in verbal kommunikasi dan sepuluh syok budaya di non-verbal komunikasi. Fungsi bahasa yang ada di verbal komiunikasi adalah sapaan, pengenalan diri, menanyakan informasi, makanan orang Bali, rumah orang Bali, transportasi, hubungan antara manusia, waktu, kebersihan, dan pemerintahan. Fungsi bahasa yang digunakan di non-verbal komunikasi adalah melambaikan tangan, menyentuh kepala, memberi jempol, banyak senyum, interaksi mata, jarak, berjabat tangan, sapaan, berpelukan, dan perbedaan antara tangan kanan dan tangan kiri. Ada beberapa cara orang Denmark mengatasi syok budaya, diantaranya adalah dengan bertanya ke orang Bali, pemandu wisata, membaca buku, dan menyesuaikan dengan budaya Bali. Kata Kunci : Syok Budaya, Non-verbal komunikasi, Verbal Komunikasi. This study aimed at analyzing the culture shock phenomena experienced by Danish tourists in Singaraja. This research was a descriptive qualitative research. The researcher analyzed the language functions of culture shock, how to adjust the culture, and how to adapt the culture. There were two forms, namely verbal communication and non-verbal communication. The subjects of this research were three Danish tourists who live in Singaraja. The data were obtained through semi-structure and semi-unstructured interview. The interview guide and voice recorder were used to collect the data. The theory was used to analyze the data was from Pederson (1995). The results of this study show that there were twenty phenomena of culture shock in verbal and non-verbal communication experienced by the Danish tourists in Singaraja. Ten culture shock phenomena were in verbal communication, and ten culture shock phenomena in non-verbal communication. The language functions of the culture shock in verbal communication were related to greeting, introduction, asking information, Balinese food, Balinese house, transportation, human relation, time management, cleanness, and government. The language function of culture shock in non-verbal communication were related to waving hands, touching head, giving thumb, more smiling, eye contact, space, shaking hand, greeting, hugging, and the different between right hand and left hand. The Danish tourists adjust their culture shock, such as asking information to local people, tour guide, reading Bali culture, and organized based on rules in Bali. keyword : Culture Shock, Non-verbal Communication, Verbal Communication.